The Effect of Tax Understanding, Tax Sanctions, and Tax Payment Awareness on Taxpayer Compliance in Jakarta - Andika Dwi Prasetyo; Zulmita Zulmita (Universitas Pancasakti Tegal, 2026)
This study aims to analyze the effect of tax understanding, tax sanctions, and tax payment awareness on taxpayer compliance registered at tax service offices (KPP) in the DKI Jakarta region. This research is motivated by the fact that taxpayer compliance levels are still not optimal despite the continuous increase in the number of registered taxpayers each year. Under the self-assessment system, taxpayer compliance is influenced by both internal and external factors, making it important to examine the determinants of tax compliance. This study employed a quantitative approach using an explanatory research method. The research data were collected through questionnaires distributed to 75 taxpayer respondents registered in the KPP area of DKI Jakarta. Data analysis was conducted using Partial Least Square Structural Equation Modeling (SEM-PLS) with the assistance of SmartPLS software. The results indicate that tax understanding has a positive and significant effect on taxpayer compliance. Tax sanctions also have a positive and significant effect on taxpayer compliance. In addition, tax payment awareness was found to be the most dominant variable influencing taxpayer compliance. Simultaneously, tax understanding, tax sanctions, and tax payment awareness affect taxpayer compliance with an R-Square value of 0.286. These findings indicate that improving taxpayer compliance can be achieved through enhancing tax understanding, strengthening tax awareness, and implementing tax sanctions consistently.